CONSUMERISM, DEBT, AND GEN Z: CAN RELIGIOSITY BE THE KEY TO BREAKING THE CYCLE? - Herlina Yustati; Yosy Arisandy; Mardian Suryani; Syafitri Anggraini; Mohd Hisyam Bin Abdul Rahim (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This research develops previous studies by integrating consumerism, religiosity, and indebtedness into a comprehensive model. By positioning religiosity as a moderator, the study provides new insights into the complex interactions affecting indebtedness. The research focused on the Gen Z demographic in Bengkulu, totaling 524,180 individuals across 9 districts and 1 city. A sample of 384 was taken using Probability Sampling. Data collection occurred through Google Form, analyzed with SEM-PLS method and second-stage models. The findings revealed a significant positive correlation between consumerism and indebtedness, indicated by a path coefficient of (0.344) and a t-statistic of (7.029) with a p-value of (0.000), suggesting higher consumerism leads to increased debtor behavior. The religiosity variable negatively influenced indebtedness, with a path coefficient of (0.112), a t-statistic of (2.171), and a p-value of (0.030), indicating that greater religiosity corresponds to lower indebtedness. Additionally, the results indicated that religiosity significantly moderates the relationship between consumerism and indebtedness, with a path coefficient of (-0.094), a t-statistic of (2.931), and a p-value of (0.003), suggesting that higher religiosity can mitigate indebted behavior. The outcomes enhance the literature with new perspectives and implications for formulating effective policies to manage indebtedness among Gen Z.